Lesbian Gay Bisexual Transgender Queer Questioning, Intersex Asexual Allies Pansexual in the Perspective of the Applicable Law in Indonesia - Permata Albuquerque, Brian; Wirya Darma, I Made (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to examine Indonesia's legal perspective on the LGBTQQIAAP community, both in existing laws and in the legislative drafts currently under discussion. This research employs a normative legal approach with a juridical-normative method, focusing on the analysis of legislation, legal doctrines, and expert opinions related to this issue. The data utilized include primary legal sources such as laws and legislative drafts, as well as secondary legal materials from literature, journals, and other academic sources. The findings indicate that the LGBTQQIAAP community in Indonesia still faces significant legal challenges that hinder the recognition and protection of their rights. Although there is no national law explicitly criminalizing their existence, various regulations and legal interpretations are often used to restrict their rights, particularly in aspects of freedom of expression and the right to live without discrimination. Legislative drafts such as the RKUHP (Revised Criminal Code) and the Family Resilience Bill have the potential to worsen this situation by reinforcing discriminatory social norms and restricting individual freedoms based on gender identity and sexual orientation. Therefore, legal reforms that are fair and based on human rights are necessary, along with educational efforts to ensure that policies reflect not only the norms of the majority but also provide equal protection for all Indonesian citizens